Integrating a Large Next-Generation Sequencing Panel into the Clinical Diagnosis of Gliomas Provides a Comprehensive Platform for Classification from FFPE Tissue or Smear Preparations. Issue 3 (28th January 2019) - Parilla, Megan; Kadri, Sabah; Patil, Sushant A; Fitzpatrick, Carrie; Ritterhouse, Lauren; Segal, Jeremy; Collins, John; Pytel, Peter
Abstract: The 2016 WHO classification of brain tumors represents a major step towards the integration of molecular data into pathologic diagnoses. Our institution has included massively parallel sequencing technology in the diagnostic work-up of all gliomas since January 2016. The utilized platform successfully identifies copy number variations, individual gene mutations, small insertions and deletions, and selected gene fusions. Herein, we retrospectively review the first 51 glial tumor samples run for clinical purposes using the UCM-OncoPlus platform, a 1213 gene targeted hybrid-capture next generation sequencing (NGS) panel. NGS paired with histomorphology and clinical data allowed for reliable, comprehensive, and cost-effective classification of all the analyzed gliomas (51/51) with minimal tissue required and without the need for additional testing. In addition to detecting all diagnostically relevant mutations according to the 2016 WHO system, our data suggest a large NGS-based platform may improve the accuracy of classifying gliomas beyond the 2016 WHO system, to provide truly personalized diagnostics. Furthermore, this methodology assists in classifying histologically challenging or clinically unusual cases. And, finally, the versatile nature of this testing methodology allows for near effortless expansion as new therapeutic targets and prognostic markers are discovered.